The Effect of E-Learning Application through the Use of Whatsapp-Assisted Edmodo on the Students’ Learning Outcomes in the Concept of Sound Waves - Mamonto, Moh. Reghi; Odja, Abdul Haris; Abdjul, Tirtawaty (Jurnal Pendidikan Fisika, 2021)
This study aims to find out the students’ learning outcomes in the application of e-learning through the use of WhatsApp-assisted Edmodo in the concept of sound waves. In addition, students' responses to the treatments given were also observed for the sake of evaluation. This research used a quasi-experimental research design carried out at SMA Negeri 1 Gorontalo in the even semester of the 2019/2020 academic year. The subject of the research was class XI IPA 8 consisting of 20 students. Tests were administered to students to obtain data of the students’ learning outcomes. The data collected were then analyzed by using normality test and statistical t-test. Based on the research results, it is known that the t-value (5.53) is greater than the t-table (1.72), so H0 is accepted and H1 is rejected. It means that there is a significant positive effect of using whatsApp-assisted edmodo on learning outcomes in the concept of sound waves. It can be seen from the difference of mean score between the pretest and posttest scores of the experimental class. Therefore, it can be concluded that the increase in students’ learning outcomes on the concept of sound waves is in the strong effect category.